Overestimation of the adaptive substitution rate in fluctuating populations. (9th May 2018) - Rousselle, Marjolaine; Mollion, Maeva; Nabholz, Benoit; Bataillon, Thomas; Galtier, Nicolas
Abstract : Estimating the proportion of adaptive substitutions ( α ) is of primary importance to uncover the determinants of adaptation in comparative genomic studies. Several methods have been proposed to estimate α from patterns polymorphism and divergence in coding sequences. However, estimators of α can be biased when the underlying assumptions are not met. Here we focus on a potential source of bias, i.e. variation through time in the long-term population size ( N ) of the considered species. We show via simulations that ancient demographic fluctuations can generate severe overestimations of α, and this is irrespective of the recent population history.